2021
DOI: 10.1101/2021.08.09.455676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human inactive X chromosome modulates expression of the active X chromosome

Abstract: Dosage compensation in humans - ensuring the viability and fitness of females, with two X chromosomes, and males, with one - is thought to be achieved chromosome-wide by heterochromatinization of one X chromosome during female development. We reassessed this through quantitative gene-by-gene analyses of expression in individuals with one to four X chromosomes, tolerance for loss-of-function mutations, regulation by miRNAs, allele-specific expression, and the presence of homologous genes on the Y chromosome. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
(233 reference statements)
1
6
0
Order By: Relevance
“…Using RNA-seq and copy number data from the TARGET Data Matrix of the leukemia cohort of n = 123 samples, we found that each inactive X in a sporadic leukemia sample was contributing on average 24.6% of the level of expression of the active X to the overall expression of USP9X in B-ALL ( Figure 4 C), which is only slightly increased compared with 14% to 17% reported in lymphoblastoid cells and fibroblasts of patients with sex chromosomal aneuploidies. 46 The level of contribution from the inactive X for gene XIST in leukemia samples (n = 127) was 100% consistent with the previously reported germline analysis ( Figure 4 D). This analysis suggests that leukemia cells retain the same state of X inactivation as found in the germline and may explain why the leukemia samples with the highest USP9X expression derive from leukemia samples with extra copies of the X chromosome in female patients.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Using RNA-seq and copy number data from the TARGET Data Matrix of the leukemia cohort of n = 123 samples, we found that each inactive X in a sporadic leukemia sample was contributing on average 24.6% of the level of expression of the active X to the overall expression of USP9X in B-ALL ( Figure 4 C), which is only slightly increased compared with 14% to 17% reported in lymphoblastoid cells and fibroblasts of patients with sex chromosomal aneuploidies. 46 The level of contribution from the inactive X for gene XIST in leukemia samples (n = 127) was 100% consistent with the previously reported germline analysis ( Figure 4 D). This analysis suggests that leukemia cells retain the same state of X inactivation as found in the germline and may explain why the leukemia samples with the highest USP9X expression derive from leukemia samples with extra copies of the X chromosome in female patients.…”
Section: Resultssupporting
confidence: 90%
“…Recent analysis performed on gene expression from X chromosomes in noncancer cells revealed that USP9X was expressed, albeit at a reduced level, from the inactive X. 46 We therefore aimed to determine whether leukemic bone marrow maintains a similar expression pattern for USP9X and other genes reported to be expressed by the inactive X. Using RNA-seq and copy number data from the TARGET Data Matrix of the leukemia cohort of n = 123 samples, we found that each inactive X in a sporadic leukemia sample was contributing on average 24.6% of the level of expression of the active X to the overall expression of USP9X in B-ALL ( Figure 4 C), which is only slightly increased compared with 14% to 17% reported in lymphoblastoid cells and fibroblasts of patients with sex chromosomal aneuploidies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In species pairs sharing an identical and chromosomal-level DC mechanism, this effect is expected to be relatively minor, since genes should not exhibit quantitative differences in the DC mechanism. However, in many species, many genes escape this global DC mechanism and exhibit gene-level expression control (85)(86)(87)(88)(89)(90)(91). These genes, if sufficiently numerous on the X could therefore also contribute to HR.…”
Section: The Overall Effect Of Strata 1 Andmentioning
confidence: 99%
“…DED1 is conserved in humans as DDX3X on the X-chromosome in females, and DDX3Y on the Y-chromosome in males. The DDX3X gene escapes X-linked inactivation and has two active alleles in most females [ 95 , 96 ]. Its male paralog, DDX3Y , shows lower and more variable expression in somatic tissues, as well as mosaic depletion with age in hematopoietic stem and progenitor cells through loss of Y [ 97 , 98 ].…”
Section: Introductionmentioning
confidence: 99%